2016
DOI: 10.1007/s00330-015-4187-0
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cytomegalovirus infection: contribution and best timing of prenatal MR imaging

Abstract: • In cCMV, isolated periventricular T2-weighted signal hyperintensity has a good postnatal prognosis. • In cCMV, SNHL and neurological impairment can be predicted at 27 or 33 weeks. • In cCMV, fetal MR has a high NPV in predicting SNHL. • In cCMV, fetal MR has a high NPV in predicting neurological impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 27 publications
6
90
1
3
Order By: Relevance
“…The most frequent finding on MRI was white matter hyperintense T2 signal. In CMV positive fetuses, Cannie et al found that isolated hyperintense T2 signal of the temporal lobe was associated with sensorineural hearing loss in 14.3% of cases, and all these babies had otherwise normal neurological outcome. These findings correlate with our study.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent finding on MRI was white matter hyperintense T2 signal. In CMV positive fetuses, Cannie et al found that isolated hyperintense T2 signal of the temporal lobe was associated with sensorineural hearing loss in 14.3% of cases, and all these babies had otherwise normal neurological outcome. These findings correlate with our study.…”
Section: Discussionmentioning
confidence: 99%
“…It can occur immediately after birth in symptomatic CMV infected children, but approximately half of reported cases of hearing loss due to cCMV infection are late-onset and, therefore, cannot always be detected at birth through newborn hearing screening (9). A recent study describes how the timing of seroconversion in primary maternal CMV infection is a strong predictor of postnatal sequelae, with a higher risk when seroconversion occurs in the first trimester rather than later in pregnancy (10). …”
Section: Discussionmentioning
confidence: 99%
“…In pregnancies with CMV-proven seroconversion, prenatal prediction of SNHL and neurological impairment by prenatal MRI showed comparable accuracy at the end of the second or in the third trimester, with a high negative predictive value. It has been shown that MRI and the time of onset of seroconversion in pregnancy are independent predictors of postnatal SNHL, and that only MRI is an independent predictor of neurological impairment (10). Furthermore, ventriculomegaly and calcifications were estimated as non-specific findings for CMV and accordingly were not graded separately (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is advised whenever fetal intracranial abnormalities are detected by US and should be performed during the third trimester (54). MRI was shown to be more sensitive than US (45), though results might be more difficult to interpret, and specialized neuroradiology consultation is required.…”
Section: Prenatal Diagnosis Of Ccmvmentioning
confidence: 99%